ANALISIS PENGARUH DAYA TARIK DESAIN PRODUK, DAYA TARIK PROMOSI, DAN PERSEPSI KUALITAS TERHADAP CITRA MEREK SERTA DAMPAKNYA TERHADAP MINAT PEMBELIAN KONSUMEN (Studi pada Calon Konsumen Honda Beat Pop di Dealer Nusantara Sakti Purwokerto) - Meiliani, Nita; Ferdinand, Augusty Tae (Faculty of Economics and Business Diponegoro University, 2016)
This study aimed to analyze the effects arising from the attractiveness of product design, attractiveness of promotion, and perceived quality on brand image and its influence on purchase intention from Honda Beat Pop motorcycle. The variables used in this study are attractiveness of design product, attractiveness of promotion, and perceived quality as an independent variable, then the brand image as an intervening variable and purchase intention as the dependent variable. This research method using a technique of sampling purposive with sample as many as 150 prospecting customer of Honda who visit to Dealer Honda Nusantara Sakti Purwokerto. Analysis method in this study used quantitive and qualitative analysis use Structural Equation Model (SEM) of the AMOS 20.0. The data is primary and uses a questionnaire with open and closed questions. The result of this research prove 3 hypothesis accepted and 3 hypothesis rejected. The 3 hypothesis accepted are show attractiveness of promotion positively affect to brand image, perceived quality positively affect to brand image, and perceived quality positively affect to purchase intention and 3 hypothesis rejected is show attractiveness of design product not significant but positively affected to brand image, attractiveness of design product not significant but positively affected to purchase intention, and brand image not significant but positively affected to purchase intention.